Investigation of the effect of speed and pressure on conductivity in inkjet printed electronic devices - ÖZCAN, ARİF (My University, 2022)
© 2022 Authors.We can define printed electronics as the application of printing on a material by means of semiconductor, dielectric and electronic components. This process basically takes place by adding materials that will provide conductivity properties into the printing inks. In addition to printing with traditional printing systems, drop-on demand inkjet printing provides an important advantage in this field thanks to its non-contact and digital patterning capabilities. Therefore, the demand for inkjet printing printable inks based on high-performance electronics is also increasing to expand the scope of possible applications for printed electronics. In recent years, inkjet printing technology has become more and more popular due to its use in various applications such as photovoltaic cells, light-emitting diodes (LED), organic thin-thin transistors, displays, radio frequency identification devices (RFID), smart clothing and sensors. For these applications, the unique feature of inkjet printing technology is that it can print on a wide range of materials and is a digital, contactless and plateless system. We can count other advantages of this technology as low cost and savings from waste. These properties make the inkjet printing technique particularly suitable for printing conductive patterns on a variety of flexible substrates in the manufacture of electronic circuits or devices. The electrical conductivity on the printed material may vary depending on the substrate, printing speed and pressure. For this purpose, a specially prepared test scale with lines of different thicknesses was printed on the polyethylene film material with BENTSAI BT-HH6105B1 Portable Handheld Mobile inkjet printing machine. The effect of machine speed and pressure values on conductivity was observed in the prints made with silver-based conductive inks. As a result, it was concluded that the conductivity value increased as the printing pressure increased at constant speed, and on the other hand, the conductivity value increased as the printing speed decreased when the pressure was fixed.
Keywords: Bilgisayar Bilimleri; Bilgisayar Grafiği; Mühendislik ve Teknoloji; Computer Sciences; Computer Graphics; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; BİLGİSAYAR BİLİMİ, İNTERDİSİPLİNER UYGULAMALAR; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; COMPUTER SCIENCE, INTERDISCIPLINARY APPLICATIONS; Bilgisayar Grafikleri ve Bilgisayar Destekli Tasarım; Fizik Bilimleri; Bilgisayar Bilimi Uygulamaları; Computer Graphics and Computer-Aided Design; Physical Sciences; Computer Science Applications; conductive ink; conductivity; inkjet; printability; printed electronics; conductivity; inkjet; printed electronics; printability; conductive ink